Seasonal pastoral exploitation of forests in the area of Subcarpathia in the 15th and 16th century - Jawor, Grzegorz (Balcanica Posnaniensia. Acta et studia, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-ansi-language: EN-US; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The arguments included in the article were based on a small number of information preserved in the sources, which concern a seasonal presence of the Wallachian shepherds in the areas situated north of the line designating the scope of permanent (year-round) rural settlements founded on the Wallachian law. It was practised both in forests belonging to the king as well as in private estates throughout all seasons. This research resulted in the thesis stating that groups of the Wallachian shepherds led a seasonal grazing of their herds in the submontane areas already in the 15th century. Various factors, primarily of an economic nature, made these pastoral activities disappear or, at least, made them significantly limited at the turn of the 16th and 17th century. Pastoralism of a transhumance type existed throughout the entire period under discussion, in modern sources referred to as koszarnictwo (transhumance herding), consisting in periodic migrations of pastoral groups from permanent villages. Similarly to what I have claimed in my previously published research on the Wallachian pastoralism in the Carpathian areas, there are no indications in the sources, which would justify a thesis for a long time widespread in historical studies, on the presence of a nomadic phase in the history of the Wallachian colonization in the Polish areas. Also in the case of the areas currently studied, its existence can be given no confirmation.